2009
DOI: 10.1016/j.neuro.2009.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Genetical toxicogenomics in Drosophila identifies master-modulatory loci that are regulated by developmental exposure to lead

Abstract: The genetics of gene expression in recombinant inbred lines (RILs) can be mapped as expression quantitative trait loci (eQTLs). So-called "genetical genomics" studies have identified locally-acting eQTLs (cis-eQTLs) for genes that show differences in steady state RNA levels. These studies have also identified distantly-acting master-modulatory trans-eQTLs that regulate tens or hundreds of transcripts (hotspots or transbands). We expand on these studies by performing genetical genomics experiments in two enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 115 publications
(119 reference statements)
4
49
0
Order By: Relevance
“…The heritability accounted for 813 pg 2 of the 2,393 pg 2 total phenotypic variance, with 309 pg 2 of the genetic variance explained by the single QTL on Chromosome II. We searched for potential candidate genes in the 50C region by correlating differences in transcription levels between control- and Pb-treated adults for each line with the mean Pb load (methods described in Ruden et al [2009] for 88 transcripts assayed in region 50C). We identified two candidate genes (CG6191-RA and CG8118) where strain differences for changes in transcription in response to Pb are significantly correlated with strain differences in Pb load (p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The heritability accounted for 813 pg 2 of the 2,393 pg 2 total phenotypic variance, with 309 pg 2 of the genetic variance explained by the single QTL on Chromosome II. We searched for potential candidate genes in the 50C region by correlating differences in transcription levels between control- and Pb-treated adults for each line with the mean Pb load (methods described in Ruden et al [2009] for 88 transcripts assayed in region 50C). We identified two candidate genes (CG6191-RA and CG8118) where strain differences for changes in transcription in response to Pb are significantly correlated with strain differences in Pb load (p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Together these mechanisms may serve to minimize Pb exposure in the brain and to offspring, especially during the first d of adult life when experience plays an important role in the development of complex behaviors (Hirsch et al, 2003). The Drosophila model facilitates extending behavioral observations to include genetic (Hirsch et al, 2009; Ruden et al, 2009) and neural mechanisms (He et al, 2009; Morley et al, 2003) mediating these effects, as well as transgenerational effects of anthropogenic Pb.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By using high-throughput microarrays analysis technologies, eQTL can be measured for many genes in the genome, rendering eQTL data information rich and potentially very powerful. Recent studies on a variety of organisms, such as yeast, Drosophila, mouse, rat, human, and plants (Brem et al 2005;Petretto et al 2006;Druka et al 2008;Veyrieras et al 2008;Ruden et al 2009;Lu et al 2011), have shown that levels of gene expression are often highly heritable Göring et al 2007;Emilsson et al 2008). Generally, it is possible for many genes to map cis-and trans-acting factors using linkage (Göring et al 2007;Emilsson et al 2008) or association mapping Stranger et al 2007a).…”
Section: Eqtl Mapping and Genetical Genomicsmentioning
confidence: 99%